Intelligent automation with IBM Cloud Pak for Business Automation : accelerate your digital transformation with IBM Cloud Pak for Business Automation /: accelerate your digital transformation with IBM Cloud Pak for Business Automation. (2023) - Chan, Allen; Trinh, Kevin; Molines, Guilhem; Samoojh, Suzette; Kinder, Stephen
No abstract available